ChemInform Abstract: Copper‐Catalyzed Radical Reactions of 2‐Azido‐N‐arylacrylamides with 1‐(Trifluoromethyl)‐1, 2‐benziodoxole and 1‐Azidyl‐1, 2‐benziodoxole. Issue 31 (14th July 2016) - Yang, Tonghao; Zhu, Haizhen; Yu, Wei
Abstract: 2‐Azido‐N‐arylacrylamides react with trifluoromethyl radicals and azidyl radicals, respectively, by using Togni′s reagent and Zhdankin′s reagent as radical sources via a tandem addition/cyclization process catalyzed by CuI.